Inquiry -based instruction in second grade classrooms in high and low socioeconomic status settings - Billman, Alison Knight (ProQuest Dissertations & Theses, 2008)
Inquiry-based instruction has a long history in education. It is a method of instruction that has been recommended across theoretical perspectives and across and within subject matter domains. Indeed, inquiry-based instruction is included in language arts, science, and social studies state standards. However, school districts face increasing demands that may lower expectations for instruction in content areas in which inquiry-based methods are more commonly recommended. Additionally, the implementation of inquiry-based instruction, like so many other kinds of instruction, may be complicated by socio-economic factors. Little is known about the amount or characteristics of inquiry-based instruction implemented in primary grades. This descriptive study sought to describe the degree and characteristics of inquiry-based instruction implemented in second grade classrooms and to describe any differences, if present, in the implementations of inquiry-based instruction in high- and low-SES classrooms. The Inquiry-based Observation Protocol (Billman, 2006) was the primary instrument used to document instruction. Results from this study indicate there is little inquiry-based instruction implemented in second grade classrooms. Inquiry-based instruction was observed during language arts, science, and social studies instruction with more inquiry-based instruction observed during language arts instruction, followed by science, and then, social studies. Proportionately, more social studies instruction used inquiry-based instructional methods. Language arts inquiry-based instruction contributed the smallest proportion of minutes to the overall total observed in that domain. Although six phases of the inquiry process were observed, nearly half of all observed inquiry-based minutes were spent collecting data. Reporting was the second most observed phase and constituted the greatest amount of time spent in social studies inquiry-based instruction. The least amount of time was devoted to analyzing or reflecting. When inquiry-based instruction was observed, there were more minutes devoted to this type of instruction in high-SES classrooms; however, that difference did not reach a level of statistical significance. Differences between groups lay in the characteristics of inquiry-based instruction. High-SES classrooms were more likely to give children opportunities to contribute to, or make decisions that determined the directions of the investigations, to make choices, and to compose text. These SES differences mirror results documented in other studies describing SES differences in classrooms and suggest that, in this case, inquiry-based instruction is implemented in ways that support social reproduction (Anyon, 1981; Duke, 2000). A number of limitations as well as directions for future research are discussed in light of these findings. The findings reported in this study suggest that further research is needed to understand what teachers know about inquiry-based instruction and how to better help them implement this method of instruction.